2013
DOI: 10.1177/1043986213507403
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Crime Online? Examining the Effect of Risk, Previous Victimization, and Exposure on Fear of Online Interpersonal Victimization

Abstract: Research exploring the extent and nature of fear of crime has spanned decades; it has been examined in many contexts, among varied populations, and from different theoretical perspectives. However, researchers have been slow to estimate or explain individuals' fear of online crime. The current study is among the first to address this issue by examining experiences from a random sample of undergraduate students enrolled at a large public university. In particular, we explore the links between perceived risk, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 43 publications
3
75
2
1
Order By: Relevance
“…Most researchers utilize 10-or 11-point scales; however, the mean levels of fear reported are relatively low, often below 5 (e.g. Fisher and Sloan 2003;Henson, Reyns, and Fisher 2013;LaGrange and Ferraro 1989). Are individuals' levels of fear really that low or do the levels of fear simply appear low because of the large scale?…”
Section: Measuring Fear Of Crimementioning
confidence: 99%
“…Most researchers utilize 10-or 11-point scales; however, the mean levels of fear reported are relatively low, often below 5 (e.g. Fisher and Sloan 2003;Henson, Reyns, and Fisher 2013;LaGrange and Ferraro 1989). Are individuals' levels of fear really that low or do the levels of fear simply appear low because of the large scale?…”
Section: Measuring Fear Of Crimementioning
confidence: 99%
“…Henson et al [5] conducted an online survey of 838 undergraduate students at a large public university that looked at the effect of perceived risk of direct, indirect, and previous Online Interpersonal Victimization (OIPV) on the fear of OIPV by an intimate partner, friend/acquaintance, and stranger. The study found that perceived risk of OIPV had positive effects on all three types of victim-offender relationships, previous direct online victimization had a positive effect on fear of OIPV by an intimate partner, previous indirect online victimization had a negative effect on fear of OIPV by intimate partners and friends/acquaintances, while online exposure (i.e., Internet usage, usage of dating sites, online groups, instant messengers, and YouTube) did not have a statistically significant effect on any of the types of victim-offender relationships.…”
Section: B Cybercrime Perceptionsmentioning
confidence: 99%
“…5 In exploratory research, structural models can be trimmed or built based on theoretical and/or empirical standards [25]. The initial model had a few non-significant effects, which were removed from the model.…”
Section: Structural Modelmentioning
confidence: 99%
“…Exploring contextual effects is important and can add to the small number of studies that have considered the potential variables influencing victimization and cyber victimization (e.g., Henson et al, 2013;Li, 2007;Roberts et al, 2013). …”
Section: Research Gapmentioning
confidence: 99%
“…The role of the internet is of particular importance when considering research into fear of cybervictimization (Henson, Reyns & Fisher, 2013). This is because both perpetrators and victims are generally heavy internet users (Walrave & Heirman, 2011) and a high prevalence of cyber-victimization exists amongst university students (Radda & Ndubueze.…”
Section: Introductionmentioning
confidence: 99%